2017
DOI: 10.3390/nu9030287
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Outcomes of the NRS 2002 in Patients Hospitalized in Nephrology Wards

Abstract: Introduction: Malnutrition is a common problem among hospitalized patients. In chronic kidney disease, it affects up to 50% of the population. Undernourishment has an adverse effect on prognosis and prolongs convalescence. The aim of the study was to test the effectiveness of NRS (Nutrition Risk Screening) -2002 in the assessment of risk of malnutrition for patients hospitalized in nephrology wards. The aim was to develop clinical characteristics of malnourished patients and to assess the relationship between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
16
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 20 publications
2
16
0
2
Order By: Relevance
“…In our study, 46 549 inpatients from five institutions were enrolled between 1 June 2012 and 31 December 2017 and followed up for 5-63 months. The patients with NRS-2002 scores ≥3 had a greater risk of AKI and longer LOS and higher mortality rates than the patients with normal nutritional status, which was consistent with previous studies that undernourished patients were generally hospitalised longer and had lower survival rates (13,38) . Without effective intervention, AKI can develop irreversibly in patients with CKD and end-stage renal disease (5) and increase mortality.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In our study, 46 549 inpatients from five institutions were enrolled between 1 June 2012 and 31 December 2017 and followed up for 5-63 months. The patients with NRS-2002 scores ≥3 had a greater risk of AKI and longer LOS and higher mortality rates than the patients with normal nutritional status, which was consistent with previous studies that undernourished patients were generally hospitalised longer and had lower survival rates (13,38) . Without effective intervention, AKI can develop irreversibly in patients with CKD and end-stage renal disease (5) and increase mortality.…”
Section: Discussionsupporting
confidence: 90%
“…The prevalence of malnutrition is 15-80 % in hospitalised patients, while only 3 % could be diagnosed and treated (8,12) . It has been reported that over 40 % of CKD patients are undernourished (13) and uraemia and dialysis can impact the nutritional status of patients with kidney disease (14,15) . AKI as the spread of inflammatory processes from the kidney to other organ systems is also affected by metabolic changes and undernutrition.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Llama la atención que nuestros resultados mostraron un alto porcentaje de riesgo nutricional en los pacientes del servicio de nefrología 95,26 % (n = 503). Esto difiere del estudio de Borek, et al (13) , el cual mostró que, utilizando la misma herramienta, 40 % de 292 pacientes admitidos de manera consecutiva durante seis meses al servicio de nefrología de un hospital universitario presentaron riesgo de desnutrición.…”
Section: Discussionunclassified
“…La población del servicio de nefrología ingresa al hospital en forma recurrente al tratamiento dialítico, lo cual puede influir en la prevalencia de riesgo encontrada. Existe evidencia de que la población nefrópata tiene un alto riesgo de desnutrición (13) relacionado con condiciones hipermetabólicas e infecciosas (14)(15)(16)(17) .…”
Section: Discussionunclassified